Creating Urban Water Resilience: Review of China’s Development Strategies “Sponge City” Concept and Practices - Roosmayri Lovina Hermaputi; Chen Hua (The Indonesian Journal of Planning and Development, 2017)
These years China's cities faced urban water security problem caused by natural disaster, man-made disaster, and water shortage. Back to the year 2002 until 2015 several cases were raised such as 2002 Guizhou Duyun slag water pollution, 2014 Lanzhou water benzene poisoning cases and the Han River Excessive Ammonia Pollution in Wuhan, Gansu Hui County blood cadmium poisoning cases. Meanwhile, a rainstorm hit Guangzhou in May 2010, Nanjing rainstorm 7.18, and recently Beijing 7.21 big rainstorm who killed about 79 people and Changsha 4.7 big flood in 2015. The "Sponge City" is the answer for China's water issues. Recorded In October 2013 Professor Lin Bingzhang recommend to build a "sponge city" as storm events and flood mitigation action, then in December, Secretary-General Xi Jinping at the central work conference on urbanisation talked about building a natural reservoir, natural infiltration, natural purification "sponge city." Followed the initiative, "Sponge City Construction Technology Guide - Low Impact Development Storm water system builders" had been released in 2014, project financing policy "Finance Building [2014] No. 838" has been established and until the year 2016, 30 cities has been chosen as sponge city urban construction pilot. The sponge city initiative aims to maximise water reservation and minimise the effects of drought and flooding by recycling and efficiently applying water supplies and reserves (AUSTRADE, 2016). This paper tries to elaborate the Sponge City theory and review of several practices in China's cities to create urban water resilience. This research will conduct theory development analysis, sponge city construction's practices analysis and its performance to actualize urban water resilience.